The magic sword - Rathborne, Basil (Narberth, Pa. : Alpha Video Distributors, 2003)
A beautiful princess is held captive by an evil sorcerer. Only a brave knight with a magic sword can save her. Based on the legend of Saint George and the dragon.
Originally produced as a motion picture in 1962.
Director of photography, Paul Vogel; music, Richard Markowitz; supervising editor, Harry Gerstad.
Keywords: George -- Saint -- 303 -- Legends; George -- Saint -- 303